Analiza danych czasowych z obserwacjami nietypowymi z wykorzystaniem metod geostatystyki - Suchecka, Jadwiga; Kowalik, Jan (The Analysis of Time Series with Outliers Using the Geostatistics Methods, 2005)
As a result of action of different external factors, such as: political and economic crises, outbreaks of wars, some observations clearly different from the others, called the outliers, appear in the economic time series. The outliers generally cause the results of conducted analyses, based on time series, are failed, unreal or even invalid. Therefore, it is important to use some appropriate procedures for detecting and eliminating those effects from time series. This paper shows the geostatistics kriging method in a detection problem of outliers in time series.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 96-105